Endoscopic-Ultrasound-Guided Fine-Needle Aspiration and the Role of the Cytopathologist in Solid Pancreatic Lesion Diagnosis. (15th May 2012) - Iqbal, Shahzad; Friedel, David; Gupta, Mala; Ogden, Lorna; Stavropoulos, Stavros N.
Abstract : Endoscopic ultrasound (EUS) is the most sensitive imaging modality for solid pancreatic lesions. The specificity, however, is low (about 75%). It can be increased to 100% with an accuracy of 95% by the addition of fine-needle aspiration (FNA). Cytopathology plays an important role. The final diagnosis is based upon the correlation of clinical, EUS, and cytologic features. A close interaction with the cytopathologist is required in improving the diagnostic yield. In this paper, we present an overview of the role of EUS-guided FNA and importance of close interaction with the cytopathologist. Day to day examples of different solid pancreatic lesions have been presented at the end.